P47(phox) IS REQUIRED FOR AFFERENT ARTERIOLAR CONTRACTILE RESPONSES TO ANGIOTENSIN II AND PERFUSION PRESSURE IN MICE - Lai, En Yin (2011)
Myogenic and angiotensin contractions of afferent arterioles generate reactive oxygen species. Resistance vessels express NOX-2 and -4. Angiotensin II activates p47(phox)/NOX-2 whereas it downregulates NOX-4. Therefore, we tested the hypothesis that p47(phox) enhances afferent arteriolar angiotensin contractions. Angiotensin II infusion in p47(phox) +/+, but not -/- mice, increased renal cortical nicotinamide adenine dinucleotide phosphate oxidase activity (7±1 to 12±1; P<0.01 vs 5±1 to 7±1; NS, 10(3) · RLU · min(-1) · μg protein(-1)), mean arterial pressure (77±2 to 91±2; P<0.005 vs 74±2 to 77±1; NS, mmHg) and renal vascular resistance (7.5±0.4 to 10.1±0.7; P<0.01 vs 7.9±0.4 to 8.3±0.4 NS, mmHg/ml·min(-1)·gkwt(-1)). Afferent arterioles from p47(phox) -/- mice had a lesser myogenic response (3.1±0.4 vs 1.4±0.2 dynes·cm(-1)·mmHg(-1); P<0.02) and a lesser (P<0.05) contraction to 10(-6)M angiotensin II (diameter change +/+: 9.3±0.2 to 3.4±0.6 μm vs -/-: 9.9±0.6 to 7.5±0.4 μm). Angiotensin and increased perfusion pressure generated significantly (P<0.05) more reactive oxygen species in p47(phox) +/+ than -/- arterioles. Angiotensin II infusion increased the maximum responsiveness of afferent arterioles from p47(phox) +/+ mice to 10(-6) M angiotensin II yet decreased the response in p47(phox) -/- mice. The angiotensin infusion increased the sensitivity to angiotensin II only in p47(phox) +/+ mice. We conclude that p47(phox) is required to enhance renal nicotinamide adenine dinucleotide phosphate oxidase activity and basal afferent arteriolar myogenic and angiotensin II contractions and to switch afferent arteriolar tachyphylaxis to sensitization to angiotensin during a prolonged angiotensin infusion. These effects likely contribute to hypertension and renal vasoconstriction during infusion of angiotensin II.